Acute heart failure: does etiology matter?. (11th May 2021) - Santos, M; Santos, H; Almeida, I; Paula, S; Miranda, H; Sa, C; Chin, J; Almeida, S; Sousa, C; Tavares, J; Santos, L; Almeida, ML
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients (pts) with acute heart failure (AHF) are a heterogeneous population. The etiology of the heart disfunction may play a role in prognosis. Risk stratification at admission may help predict in-hospital complications and needs. Objective: To explore predictors of in-hospital mortality (IHM), post discharge early mortality [1-month mortality (1mM)] and late mortality [1-year mortality (1yM)] and early and late readmission, respectively 1-month readmission (1mRA) and 1-year readmission (1yRA), in our center population, using real-life data. Methods: Based on a single-center retrospective study, data collected from patients (pts) admitted in the Cardiology department with AHF between 2010 and 2017. Pts without data on previous cardiovascular history or uncompleted clinical data were excluded. The pts were divided in 3 groups: ischemic etiology (IE), valvular etiology (VE) and other etiologies (OE), which included hypertensive and idiopathic cardiomyopathies). Statistical analysis used non-parametric tests and Kaplan-Meyer survival analysis. Results: We included 300 pts admitted with AHF. Mean age was 67.4 ± 12.6 years old and 72.7% were male. 37.7% had previous history of revascularization procedures, 66.9% had hypertension, 41% were diabetic and 38% had dyslipidaemia. The heart failure was of IE in 45%, VE in 22.7% and of OE in 32.3% of the cases. There were no significant differences between groups regarding body mass index, Killip-Kimball class, systolic blood pressure at admission, blood tests aspects at admission (namely, creatinine, sodium or urea), inotropes' usage or need of non-invasive or invasive ventilation. However, IE group had higher percentage of males comparing to VE e OE (83.0% vs 55.9% vs 70.1%, respectively, p < 0.001), higher rates of prior revascularization procedures (68.9%, vs 19.1%, vs 7.2%, p < 0.001) and higher rates of traditional cardiovascular risk factors, namely hypertension (74.1% vs 55.9% vs 57.7%, p = 0.014), diabetes mellitus (48.1% vs 27.9% vs 27.8%, p = 0.002) and dyslipidaemia (48.9% vs 30.9% vs 40.2%, p = 0.022). OE group was younger compared to IE and VE (63.9 ± 13.5 vs 68.9 ± 11.1 vs 69.5 ± 13.0 years old, respectively, p = 0.003). VE group had less left ventricle disfunction comparing to IE and VE groups (left ventricle ejection fraction 40.8 ± 14.1 vs 32.2 ± 9.8 vs 31.6 ± 12.8%, respectively, p < 0.001). The groups showed no significant differences regarding IHM (IE 5.2% vs VE 8.8% vs OE 2.1%, p = 0.146), 1mRA (IE 8.1&, VE 7.4%, OE 3.1%, p = 0.276) or 1yRA (IE 55.6%, VE 54.4%, OE 47.4%, p = 0.449). However, VE group had higher rates of 1mM (VE 13.2% vs IE 8.9% vs OE 3.1%, p = 0.05) and 1yM compared to IE and OE (33.8% vs 30.4% vs 17.5%, respectively, p = 0.34). These aspects are represented in Kaplan Meier survival curves. Conclusion: In our population, the etiology of heart failure was predictor of early and late post-discharge mortality but not readmission.